Analysis of Health Services Based on the BPJS Program in Hospitals - Ganda Agustina Hartati Simbolon; Nasrullah Nasrullah; Poniyah Simanullang; Bernadetha Bernadetha; Jean Henry Raule (Jurnal EduHealth, 2023)
This study aimed to determine health services based on the BPJS program in hospitals. This type of research is a quantitative observational study with operational research and survey designs, and data collection is cross-sectional. The population is all BPJS Kesehatan patients who visit or register at Praya General Hospital in the period February-May 2023. Sampling was done using a purposive sampling method. According to the researchers' objectives, respondents were taken from all visitors on service days between Monday and Thursday. The minimum number of samples taken is 5% of the average daily patient visits, namely 5% x 410 = 21 or 84 patients for four working days. Its realization for system analysis obtained a sample of 100 for each service counter, and for the patient perception study, a sample of 94 respondents was collected. Sample inclusion is a patient who is willing and able to be interviewed. The results of this study are the overall satisfaction aspect indicating that 50 respondents (60.0%) were very satisfied with the overall service provided by Praya General Hospital, while 35 respondents (48.0%) were dissatisfied. Customer expectations show that 27 respondents (33.0%) strongly agree that the services provided by Praya General Hospital meet patient expectations, while 18 strongly agree. Respondents (30.0%) indicated that they disagreed with this statement. Places of Interest Repurchasing showed that 12 respondents (26.0%) strongly agreed that they would return to Praya Hospital if they needed treatment, and 14 respondents (14.0%) said they did not plan to return for treatment. Based on the results of interviews with patient testimonials from hospital services, they said the following: In the service process, patients have to wait a long time before arriving at the ward. According to one patient (Ida) who complained and said that she had cancer for up to 9 consecutive days for class I (queue number 9) because the doctor said that the patient would be operated on when they got a room. In addition, patients report to the BPJS representative office located at Praya General Hospital, where patients receive referrals. It is clear from the patient's statements that the responsibility of BPJS officers is unfair to the complaints experienced by many patients.